Penerapan Metode Drill pada Bilangan Operasi Hitung Matematika terhadap Hasil Belajar Siswa Kelas 2 di MI Munada Sungai Nibung - Mustamiah; Hanif Amrullah ZA; Nurul Aisyah (CV. Creative Tugu Pena, 2025)
This study aims to ascertain the application of the drill method in mathematics education, specifically concerning arithmetic operations for second-grade students at MI Munada Sungai Nibung. Observations indicate persistent challenges in mathematics learning, notably the subpar academic outcomes attained by students. A contributing factor is the insufficient innovation from educators in devising engaging and effective teaching methodologies. The research employs a qualitative descriptive approach, utilising observation, interviews, and documentation for data collection. The findings demonstrate that the implementation of the drill method significantly enhances students' speed and accuracy in solving mathematical problems. The procedural steps integral to the drill method—such as establishing associations, clarifying objectives, motivating students, facilitating repeated practice, applying concepts, conducting evaluations, and implementing follow-ups—effectively support students in mastering arithmetic operations. Furthermore, a conducive learning environment and the incorporation of teaching aids bolster student engagement and confidence. In conclusion, the drill method can effectively enhance students' comprehension and academic performance in mathematics in a manner that is both enjoyable and productive. This study contributes by outlining a more systematic and engaging drill method tailored for elementary school students. The outcomes provide practical guidance for educators aiming to implement the drill method to improve learning results while fostering student motivation and self-assurance.